THE LEGAL NATURE OF CIVIL RIGHTS AS A THEORETICAL CONCEPT - Kaliuzhnyi, Rostyslav; Oleshchenko, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose is aimed at studying the legal nature of civil rights. Research methods: applied general scientific and special legal methods of scientific knowledge, in particular: system-structural method, observation method, generalization method, methods of analysis and synthesis. Results: сivil rights have a rather complex legal nature to give them a single general characteristic. Nevertheless, according to the results of the study, the following features can be determined: 1. Civil rights are rights that ensure non-interference on the part of the state, but at the same time, without a state that determines the legal status of a person, these rights cannot be realized. 2. Depending on the rights that a person realizes, he may be in different statuses - negative (or free), active, positive status of a person. 3. Civil rights are declarative. It does not matter whether a person uses them or refrains from using them, they should always be under the protection of the state. Discussion: it is determined that the complex legal nature of civil rights creates limited opportunities for their interpretation and classification and further protection. It is also established that civil rights are rights with a long and complex history of their formation, which should be taken into account in modern legislative changes. The complex legal nature of civil rights causes the absence of a single generally defined terminological interpretation of civil rights, as well as their classification. In turn, this has a negative impact on the ability to protect these rights, as well as conducting monitoring studies to measure the level of security and the number of violations. It is necessary to conduct further research in this direction.